A Novel Rare Earth Ion Fluorescent Probe towards the Trace Detection of 2,4,6-Trinitrotoluene Based on Fluorescence Resonance Energy Transfer - Wang, Xianqin; Chen, Hong; Zhang, Hui; Sun, Hong; Zhang, Lingyun; Zhu, Dechun; Gao, Daming (Asian Journal of Chemistry, 2014)
This paper reports a resonance energy transfer-fluorescence quenching of the core-shell structure of CaMoO4:Tb3+@SiO2 modified by amino group on the surface for the ultrasensitive and ultratrace detection of 2,4,6-trinitrotoluene (TNT) in solution environments. Organic amine was covalently modified onto the surface of silica shell to form a hybrid monolayer of amino group. The particle can specifically bind TNT species by the charge-transfer complexing or acid-base pairing interactions between electron-rich amine ligands and electron-deficient aromatic rings. The resultant TNT-amine complexes bound at the silica surface can strongly suppress the fluorescence emission of the chosen dye by the fluorescence resonance energy transfer (FRET) from CaMoO4:Tb3+ fluorescence donor to the irradiative TNT-amine acceptor through intermolecular polar-polar interactions at spatial proximity. The nanoparticle can sensitively detect down to 1 nM TNT with the use of only 10 μL of solution (2 pg TNT). The simple FRET-based nanoparticle sensors reported here exhibit a high and stable fluorescence brightness, strong analyte affinity and good assembly flexibility and can thus find many applications in the detection of ultratrace analytes.